2004
DOI: 10.4049/jimmunol.173.8.4919
|View full text |Cite
|
Sign up to set email alerts
|

Blocking Programmed Death-1 Ligand-PD-1 Interactions by Local Gene Therapy Results in Enhancement of Antitumor Effect of Secondary Lymphoid Tissue Chemokine

Abstract: The negative signal provided by interactions of programmed death-1 (PD-1) and its ligands, costimulatory molecules PD-L1 (also B7-H1) and PD-L2 (also B7-DC), is involved in the mechanisms of tumor immune evasion. In this study, we found that this negative signal was also involved in immune evasion in tumor immunotherapy. When we used different doses of a constructed eukaryotic expression plasmid, pSLC, which expresses functional murine secondary lymphoid tissue chemokine (SLC, CCL21), to treat BALB/c mice inoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
119
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 115 publications
(121 citation statements)
references
References 46 publications
2
119
0
Order By: Relevance
“…Many groups of investigators have reported that blockade of the PD-1/PD-L1 interaction promotes tumor immunity. [35][36][37] Conversely, there remains a problem regarding PD-1/PD-L1 blockade because of the possible expansion of poorly immunogenic cells. 38 Further studies may be required to clarify the therapeutic effect of PD-1/PD-L1 blockade in malignant melanoma models and clinical trials.…”
Section: Pd-l1 Expression In Malignant Melanomamentioning
confidence: 99%
“…Many groups of investigators have reported that blockade of the PD-1/PD-L1 interaction promotes tumor immunity. [35][36][37] Conversely, there remains a problem regarding PD-1/PD-L1 blockade because of the possible expansion of poorly immunogenic cells. 38 Further studies may be required to clarify the therapeutic effect of PD-1/PD-L1 blockade in malignant melanoma models and clinical trials.…”
Section: Pd-l1 Expression In Malignant Melanomamentioning
confidence: 99%
“…The expression of B7-H1 on melanoma cells were examined by FACS analysis as described previously. 25 …”
Section: Preparation Of Hsp70-melanoma Peptide Complexmentioning
confidence: 99%
“…25 The expression plasmid pMSH70 of human HSP70 was kindly provided by Dr. Richard Morimoto and Ji-zhong Cheng (The University of Texas Medical Branch). Plasmid DNA was prepared by selective compaction with spermine (Sigma) and endotoxin levels were less than 3 pg/lg of plasmid DNA as determined by Limulus amebocyte lysate assay (BioWhittaker, Walkersville, MD).…”
Section: Plasmidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunohistochemistry was performed with the method of SP, as described (Wiendl et al, 2002;He et al, 2004). Goat anti-mouse PD-1 antibody (R&D systems Minneapolis, CA) was used to detect PD-1 expression at a dilution of 1: 200.…”
Section: Immunohistochemistry (Ihc) Analysis Spd-1 Expression On H22 mentioning
confidence: 99%